Surface CO2 system dynamics in the Gulf of Anadyr during the open water season. (15th March 2021) - Pipko, Irina I.; Pugach, Svetlana P.; Luchin, Vladimir A.; Francis, Oceana P.; Savelieva, Nina I.; Charkin, Alexander N.; Dudarev, Oleg V.; Semiletov, Igor P.
Abstract: The Gulf of Anadyr (GA), one of the largest and most poorly investigated gulfs of the Bering Sea, is an important part of the Pacific Arctic. Drivers and mechanisms responsible for the spatial variations in surface seawater CO2 system parameters and associated air–sea CO2 fluxes were investigated during three oceanographic cruises conducted in the GA during the open water season of 1992, 2002, and 2011. It was shown that the surface waters of the GA were moderate to strong sinks for atmospheric CO2 during this season: mean air-sea CO2 fluxes for the investigated areas of the GA, for the three cruises, were −31, −15, and −30 mmol CO2 m −2 d −1, respectively. The summer air-sea CO2 flux was attributed to intensive phytoplankton bloom, and fall CO2 uptake coincided with a period of strong winds and seasonal enhanced primary production. The surface waters of the GA were supersaturated with respect to aragonite during the investigated period. Anadyr Strait, a region of high hydrodynamic activity, was the only area where CO2 efflux was observed. Surface waters of the strait were supersaturated with respect to CO2 and in quasi-equilibrium with respect to aragonite. We found that during the late summer/fall season, the Anadyr Current exported a well-mixed, relatively cold, salty, nutrient- and CO2 -rich water through the western Anadyr Strait into the Chirikov Basin. Our research highlights the need for mesoscale studies of the western Bering Sea to produce the most accurate assessment of the regional CO2 budget. Highlights: Drivers responsible for the spatial variations in seawater CO2 system and CO2 fluxes for the Gulf of Anadyr are identified. Decisive impact of the biological factor on the variability of p CO2 in the surface waters during open water season is shown. Calculated air-sea CO2 fluxes indicate the region is a large sink for atmospheric CO2 during open water season.